Preserving the Ocean Circulation: Implications for Climate Policy - Klaus Keller; Kelvin Tan; Francois M.M. Morel; David F. Bradford (Center for Economic Studies and ifo Institute (CESifo), 1999)
Climate modelers have recognized the possibility of abrupt climate changes caused by a reorganization of the North Atlantic's current pattern (technically known as a thermohaline circulation collapse). This circulation system now warms north-western Europe and transports carbon dioxide to the deep oceans. The posited collapse of this system could produce severe cooling in north-western Europe, even when general global warming is in progress. In this paper we use a simple integrated assessment model to investigate the optimal policy response to this risk. Adding the constraint of avoiding a thermohaline circulation collapse would significantly reduce the allowable greenhouse gas emissio ns in the long run along an otimal path. Our analysis implies that relatively small damages associated with a collapse (less than 1% of gross world product) would justify a considerable reduction of future carbon dioxide emissions.
Keywords: 330